The effect of Qur’anic readings in directing the parsing of the present tense verb in Surat Al Imran - Arif Karim Kahar Al-Jubouri (Journal of College of Education, 2024)
This research, which was titled (Parsing the present tense verb in Surat Al Imran), dealt with the structure of the present tense verb in the Arabic language in general, and in Surat Al Imran. Imran in particular, then I counted the number of verbs that appeared in this blessed Surah, in terms of their triple past tense, and not The trio, and the research showed the temporal significance of the present tense verb in the Arabic language, and since the grammarians agreed on one opinion regarding the construction of the past tense verb and the construction of the imperative verb, they also followed the same agreement that the present tense verb Ra’a is Arabized, but they differed as to why it was Arabized. The research aimed to Investigating this reason over which they disagreed. The research also directed the parsing of the present tense verb in the nominative, accusative, and genitive in the light of the Qur’anic readings in Surat Al Imran. Then, in the pages of this research, I studied what I found of the parsing of this verb in the blessed Surah by Rather, directing the different readings in it, The latter has a significant impact on changing the semantic meaning of the Qur’anic text within the context
Keywords: parsing, present tense, Surah Al Imran, guidance, Quranic readings